Urban home: young male migrants constructing home in the city. - Fathi, Mastoureh; Ní Laoire, Caitríona (Journal of Ethnic & Migration Studies, 2023)
This paper offers an exploration of the concept of 'urban home' (or, constructing home in city space) by focusing on two groups of young male migrants: refugees and international students in Cork, Ireland. Walking methods and photography were used to record migrants' geographies of urban home through the lens of everyday inhabitance of the city. We propose four dimensions to the construction of urban home in post-migration lives – instrumentality, memory, spaces of care, and future home. Our analysis shows that migrants connect to and disconnect from the city of Cork in different ways. Young male migrants in this study feel largely disconnected from hegemonic Irish society and, as such, much of their meaning-making of home is shaped in relation to an unknown postponed and undefined future time. Urban home here is not an attachment to Cork city as home, but, rather to a familiar idea of home that may take place in Cork.